THE EFFECTIVENESS OF THE ORGANI- ZATION OF ACTIVITIES OF INSURANCE INTERMEDIARIES IN THE DEVELOP- MENT OF INSURANCE NETWORKS - Khurshidovich, Abdurakhmonov Ilyos; Ergashevich, Beknazarav Zafar; Polatovich, Tursunov Jahongir (International Journal of Psychosocial Rehabilitation, 2020)
In this article, the organizational legal basis of insurance intermediaries in the market of Insurance Services was analyzed, the description of insurance intermediaries, as well as the foil of insurance intermediaries of a developed foreign state, their classification and classification, the views of economists on the subject, the tariffs and problems given to insurance intermediaries were analyzed. Based on the above analysis, scientific proposals and practical recommendations on further development and improvement of the activities of insurance intermediaries have been developed.